Ratification and Reservations: A Window-Dressing Exercise? A Study on Reservations to Human Rights Treaties - Egelberg,Sara (2021)
For the conditions under which States may reserve themselves to certain provisions of a Convention, which they nevertheless wish to oblige themselves to, are regulated in Article 19 VCLT. States may make reservations under this Article unless: (a) a reservation is prohibited by the treaty, (b) the treaty provides that only reservations of a certain kind – and the reservation in question is not of that kind, or (c) the reservation is incompatible with the object and purpose of the treaty. The latter gives rise to certain problems in relation to human rights treaties in the light of the fact that there is a desire for universal ratification of these treaties, and hence an incentive to adopt an approach of greater flexibility in cases of these kind of treaties. In the Advisory Opinion of the ICJ from 1951, which addresses the issue of reservations to the Convention against Torture and subsequently provided the groundwork for the provision in the VCLT, the Court stated that a reservation is permissible as long as the reservation is not incompatible with the object and purpose of the treaty. In cases where a State asserts that it can make any reservation it desires in view of its sovereignty, these reservations must be assessed on a case-by-case basis. The possibility of objecting to reservations is further regulated in Article 20 VCLT. The ICJ stated in its Advisory Opinion that an objecting State may, if it so desires, opt not to consider the reserving State as a party to the Convention. The effect of a State not being considered a party to the Convention differs depending on whether it is a commercial treaty or a human rights treaty, as the latter does not have reciprocal effect. The inhabitants of the State – who are not subject to international law – are the beneficiaries of the rights established in human rights treaties. It is thus not a question of exchanging rights and obligations between States, but for the State to provide these rights to their citizens. Due to the absence of a bilateral consequences, States often lack the incentive to object to other States’ reservations – even though they may be considered as incompatible with the object and purpose of the treaty. Furthermore, even if they do, it seldom implies any effect for the subjects to the rights of the reserving State, unless the State withdraws its reservation. This raises the issue of the integrity of a treaty versus the prospect of universal ratification in order to extend the scope of the treaty. Regardless of the subjective answer to this question, which cannot be said to have a definite answer, it however becomes clear that general reservations, in which States reserve themselves against core Articles for the object and purpose of the treaty, inhibit the scope of the treaty’s object and purpose and are permissible despite their incompatibility. This is primarily owing to the fact that the ICJ’s Advisory Opinion had a bigger influence than it may had anticipated, and that the VCLT, which codified the Court’s established rule, is based on a bilateral model, and so the implications of the acquis differ significantly when applied to multilateral treaties. The safety net in terms of objections to reservations practically ceases to exist, which has the consequence that reservations, which are inherently impermissible, are accepted. States that, e.g., reserve themselves to a general provision obligating the contracting parties to abolish discrimination against women may continue to be a State party to the the Convention on the Elimination of all Forms of Discrimination Against Women and enjoy the benefits it entails, whilst the inhabitants of the State may not enjoy the fundamental rights that the Convention aims to guarantee.
Keywords: Public international law; reservations; human rights treaties; treaties; human rights